A Policy Study on the Implementation Challenges of Phytosanitary Standards: The Case of ISPM 15 in Botswana, Cameroon, Kenya, and Mozambique. (June 2019) - Papyrakis, Elissaios; Tasciotti, Luca
The rise in international trade in recent decades has been accompanied by an increase in the movement of wood packaging materials (WPMs). Recognizing the associated threat of cross-border pest movement, the Commission on Phytosanitary Measures, the governing body of the International Plant Protection Convention, adopted the International Standards for Phytosanitary Measures No. 15 (ISPM 15; guidelines for regulating WPM in international trade) for the treatment of WPMs. The objective of this article is to raise awareness on the challenges four sub-Saharan countries—Botswana, Cameroon, Kenya, and Mozambique—are facing when it comes to implementation. During extensive fieldwork, we conducted interviews with key stakeholders to understand their role in the setup and implementation of the standard as well as their perceptions on relevant challenges. Addressing these challenges is vital for achieving compliance and removing associated institutional and economic barriers. The article can assist policy-makers and academics to design future policies that tackle implementation problems, especially in the context of developing countries.